Effectiveness of the proprioceptive neuromuscular taping in patients with chronic mechanical neck pain at a state hospital in Lima, Peru - Del Aguila Torres, Violeta (2020)
Objective: To determine the influence of applying a proprioceptive neuromuscular taping (VNP) on patients with chronic mechanical neck pain (DCMC) at a state hospital in Lima, Peru. Materials and methods: A quantitative-approach, quasi-experimental, longitudinal, prospective study conducted between April and June 2018. The sample consisted of 30 patients divided into two groups of 15 participants each: an experimental group (in whom the VNP was applied) and a control group (in whom the conventional treatment was applied). Both groups underwent a pretest and a posttest. Pain was evaluated by the analogue pain scale and the degree of disability was measured by the neck disability index questionnaire. The statistical analysis was performed using the Stata 13 program and the Student’s t-test, which confirms that there is a significant difference between the pretest and posttest averages. Results: The application of the VNP statistically influences the reduction of the chronic mechanical neck pain (p = 0.000) and the improvement of the neck disability index (p = 0.000). Conclusions: A statistically significant influence was shown on the reduction of neck pain and the disability index in patients with DCMC. Therefore, this medical procedure should be taken into consideration as part of the DCMC treatment.